Close Contact; Specification & Implementation - Malik, Md. Fahad Salman (My University, 2009)
Close Contact is a web application which is the product of Euroway Media. It is a Business To Business application, its focus is to provide marketing facilities to its customers (users). The users of the Close Contact will use this web application to send promotions and newsletters to their potential customers. These customers include both industrial clients and then can be distributed by them for their sub clients as well. The goal of this thesis is actual realization of the features put forth by the Euroway Media which include newsletters, SMS promotions & user behavior by use of statistics. All details related to specification and implementation will be the part of this thesis and will be discussed here. This document cover the features, conceptual model, use cases, architecture, database model, screen analysis and test cases of Close Contact. After the initial analysis and design the implementation part was started on the finalized design. As Euroway Media works in PHP for all of its implementation so we also used PHP for the creation of Close Contact.
Keywords: Datavetenskap (datalogi); Computer Science